Implementation of Storytelling Technique to Improve Speaking Skill - Pricilla Oktavia Kaet; Edmundus Bouk; Erlinda Sonya Pale (Universitas Nurul Jadid, 2023)
The target of speaking skills is difficult to achieve in junior high school, since instruction and learning of speaking can present certain challenges for teachers and students. Therefore, this study aims to explore how storytelling affects students' speaking skills and how they feel about using storytelling technique. This research was conducted in class VIII Kefamenanu middle school. This current research utilized classroom action research in which interview and observation were the instruments to use in obtaining necessary data. The mean score from the results of the implementation of the first cycle test was 59.67 and 75.21 for the second cycle, which experienced an increase. Thus, the result indicated that storytelling technique was an effective way to upgrade students’ speaking skill. In addition, storytelling techniques allow the students to speak more clearly and they also gain more confidence in practicing their English.